Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1029/gl016i012p01363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metals on the rate of the oxidation of H2S in seawater

Abstract: Recent measurements on the oxidation of H2S in the Black Sea yielded rates that were ten times faster than expected. To determine if this increase was due to trace metals, measurements have been made on the oxidation of H2S in seawater with added transition metals. Below a concentration level of 100 nM, none of the metals except Fe2+ affect the rate of oxidation. At higher concentrations the rates increase for all the metals except Zn2+. The increase in the rates followed the order. The increase in the rates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 19 publications
3
58
1
Order By: Relevance
“…Using a photomultiplier tube sensitive to the wavelengths 380-620 nm, they observed greater luminescence with higher sulfide concentrations (Figure 2.10) [Tapley, 1993]. They also noted decreased emission with the presence of a chelator, which supports the findings that metal catalysis plays a role in sulfide oxidation [e.g., Chen et al, 1972;Vazquez et al, 1989]. Indeed, as noted by Tapley et al [1999], hydrothermal vent fluids contain significant concentrations of sulfide and undergo rapid mixing with oxygenated seawater entrained in the vent plume.…”
Section: Tribo-and Crystalloluminescencesupporting
confidence: 68%
“…Using a photomultiplier tube sensitive to the wavelengths 380-620 nm, they observed greater luminescence with higher sulfide concentrations (Figure 2.10) [Tapley, 1993]. They also noted decreased emission with the presence of a chelator, which supports the findings that metal catalysis plays a role in sulfide oxidation [e.g., Chen et al, 1972;Vazquez et al, 1989]. Indeed, as noted by Tapley et al [1999], hydrothermal vent fluids contain significant concentrations of sulfide and undergo rapid mixing with oxygenated seawater entrained in the vent plume.…”
Section: Tribo-and Crystalloluminescencesupporting
confidence: 68%
“…free sulfide Vazquez et al, 1989 . It is therefore likely that the presence of sulfide in seawater is the result of a steady state of on-going processes of Ž production such as in flocs of bacteria and other .…”
Section: Copper Speciationmentioning
confidence: 99%
“…tion by metals demonstrated that copper II monobisulfide has a higher oxidation rate than free sulfide, and that Zn 2q is more likely to stabilise sulfide Ž . Vazquez et al, 1989 . Voltammetry was used to monitor the distribution of sulfide in the water col-Ž .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Dissolved sulfide present in the oxic surface water of open oceans has been thought to be due to the formation of stable metal-sulfide complexes, such as ZnHS + . 21,22 However, the reason why dissolved sulfide exists stable in the oxic epilimnionic water of Lake Nakaumi remains unsolved. Further studies on the behavior of dissolved sulfide in the lake are currently in progress, and the results will be reported elsewhere.…”
Section: Application To Environmental Watersmentioning
confidence: 99%